Psychopaty of The Main Character in The Collection Short Stories Perempuan Yang Menunggu by DM Ningsih - Raja Syamsidar; Laras Tri Handayani; Tengku Muhammad Sum (Universitas Pendidikan Muhammadiyah (UNIMUDA) Sorong, 2023)
This research is entitled Psychopathy of the main character in a collection of women's short stories waiting for DM Ningsih's work in terms of literary psychology. Psychopathy is a personality disorder characterized by a group of behaviors and traits, including ego, deceit, shallow emotions, lack of guilt, remorse, empathy and an anti-social lifestyle as well as a tendency to ignore or violate social conventions and rules. This study aims to describe the psychopathy of the main character in a collection of short stories by DM Ningsih with a literary psychology approach, using Sigmund Freud's psychoanalytic personality theory in particular, namely Personality Structure and Psychopathy-Checklist Revised Hare. The results of this study are (1) The form of psychopathic behavior of the main character in DM Ningsih's short story collection is based on the characteristics of the special actors in psychopaths, namely antisoacial behavior, likes to manipulate, aggressive behavior, sadistic behavior, and no regrets and no guilt so that the form of behavior can be determined psychopath. (2) the factors that cause the main character to behave psychopathically in DM Ningsih's short story collection are environmental and traumatic factors.